Conjugated diene polymer, polymer composition, crosslinked product, and tire

By preparing specific conjugated diene polymers and crosslinkers, the existing rubber materials are solved to take into account the strength and environmental friendliness, and the effect of high strength and efficient resource utilization is achieved.

CN119790085APending Publication Date: 2025-04-08ENEOS MATERIALS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380062384.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing rubber materials are difficult to balance between high strength and environmental friendliness, especially the problem of maintaining resource utilization efficiency while improving strength.

Method used

By preparing a conjugated diene-based polymer, the repeating units of the polymer contain 45% to 99% of the conjugated diene compound, 0% to 40% of the aromatic vinyl compound and 1% to 30% of the monomer with a specific partial structure, the crosslinking agent and filler are combined to form a high-strength crosslinking object.

Benefits of technology

It realizes high strength and efficient resource utilization of rubber materials, is suitable for high-performance rubber products such as tires, and improves the mechanical strength and wear resistance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790085A_ABST
    Figure CN119790085A_ABST
Patent Text Reader

Abstract

The present invention is a conjugated diene polymer and a cross-linked product obtained by cross-linking the polymer, the conjugated diene polymer has 45-99 mass% of a repeating unit (a) derived from a conjugated diene compound, 0-40 mass% of a repeating unit (b) derived from an aromatic vinyl compound, and 1-30 mass% of a repeating unit (c) having a partial structure represented by formula (1) with respect to all repeating units. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS]

[0002] This application claims priority based on Japanese Patent Application No. 2022-147890 filed on September 16, 2022, the entirety of which is incorporated herein by reference.

[0003] The present invention relates to a conjugated diene polymer, a polymer composition, a cross-linked product and a tire. Background Art

[0004] Conjugated diene polymers such as styrene butadiene rubber (SBR) are widely used in various rubber products such as pneumatic tires, anti-vibration rubbers, and hoses due to their excellent properties such as heat resistance, wear resistance, mechanical strength, and moldability. In general, conjugated diene polymers are produced by emulsion polymerization or solution polymerization.

[0005] Patent Document 1 discloses a modified conjugated diene polymer containing butadiene units and styrene units and having modified terminals as a conjugated diene polymer produced by solution polymerization. Patent Document 2 discloses a silica-filled rubber composition obtained by emulsion polymerization using 1,3-butadiene and styrene, containing the conjugated diene polymer obtained therefrom, a cationic polymer such as polydiallylmethylamine and its ammonium salt, and silica.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2019-182996

[0009] Patent Document 2: Japanese Patent Application Publication No. 2004-256801 Summary of the invention

[0010] Problems to be solved by the invention

[0011] As consumers' awareness of the environment increases, rubber materials are required to have higher strength in order to save resources.

[0012] The present disclosure has been made in view of the above-mentioned problems, and a main object of the present disclosure is to provide a high-strength cross-linked product and a conjugated diene polymer capable of obtaining a high-strength cross-linked product.

[0013] Technical means of solving problems

[0014] According to the present disclosure, in one embodiment, a conjugated diene polymer can be provided, which has 45% to 99% by mass of repeating units (a) derived from a conjugated diene compound, 0% to 40% by mass of repeating units (b) derived from an aromatic vinyl compound, and 1% to 30% by mass of repeating units (c) derived from a monomer having a partial structure represented by the following formula (1), relative to all repeating units.

[0015] [Chemistry 1]

[0016]

[0017] (In formula (1), n ​​is 0 or 1, R 1 represents a single bond or an alkylene group having 1 to 20 carbon atoms, R 2 ~R 4 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and "*" represents a bond to the polymer main chain)

[0018] According to the present disclosure, in another embodiment, a polymer composition containing the conjugated diene polymer and a cross-linking agent may be provided.

[0019] In addition, according to the present disclosure, in yet another embodiment, a cross-linked product obtained from the polymer composition may be provided.

[0020] Furthermore, according to the present disclosure, in yet another embodiment, a tire at least partially using the cross-linked product may be provided.

[0021] Effects of the Invention

[0022] According to the present disclosure, a conjugated diene polymer capable of obtaining a high-strength cross-linked product can be provided. DETAILED DESCRIPTION

[0023] Hereinafter, matters related to the implementation of the present disclosure will be described in detail. In addition, in this specification, the numerical range recorded using "to" means that the numerical values ​​recorded before and after "to" are included as the lower limit and the upper limit. The present disclosure should be understood as not being limited to the implementation described below, but also including various modifications implemented within the scope of not changing the gist of the present disclosure.

[0024] 《Conjugated diene polymers》

[0025] The conjugated diene polymer disclosed in the present invention is a polymer (hereinafter also referred to as "polymer (P)") having 45% to 99% by mass of repeating units (a) derived from a conjugated diene compound, 0% to 40% by mass of repeating units (b) derived from an aromatic vinyl compound, and 1% to 30% by mass of repeating units (c) having a partial structure represented by the formula (1) relative to all repeating units. Polymer (P) is described in detail below.

[0026] Repeating unit (a)

[0027] Repeating unit (a) is a structural unit derived from a conjugated diene compound. As a conjugated diene compound, for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 1,3-heptadiene, 2-phenyl-1,3-butadiene, 3-methyl-1,3-pentadiene, 2-chloro-1,3-butadiene, etc. Among these, 1,3-butadiene, isoprene, and 2,3-dimethyl-1,3-butadiene are preferred, and 1,3-butadiene is particularly preferred in terms of being able to improve processability and reduce hysteresis loss in a balanced manner. The conjugated diene compound constituting the repeating unit (a) may be one or more.

[0028] In polymer (P), the content of repeating unit (a) is 45% to 99% by mass relative to the total amount of repeating units constituting polymer (P) (hereinafter also referred to as "total repeating units"). If the content of repeating unit (a) is less than 45% by mass, there is a tendency that the processability and low hysteresis loss characteristics are insufficient when applied to tire applications. In addition, if the content of repeating unit (a) exceeds 99% by mass, there is a tendency that the content of repeating unit (c) in polymer (P) is small, and the improvement effect of strength brought about by the introduction of repeating unit (c) cannot be fully obtained. Therefore, relative to the total repeating units of polymer (P), the content of repeating unit (a) is preferably 48% by mass or more, more preferably 55% by mass or more, further preferably 60% by mass or more, and further preferably 65% ​​by mass or more. In addition, relative to the total repeating units of polymer (P), the content of repeating unit (a) is preferably 95% by mass or less, more preferably 90% by mass or less.

[0029] Repeating unit (b)

[0030] Repeating unit (b) is a structural unit derived from an aromatic vinyl compound. As an aromatic vinyl compound, for example, styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, tert-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl) dimethylaminoethyl ether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-tert-butylstyrene, 3-tert-butylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, vinylxylene, vinylnaphthalene, vinylpyridine, diphenylethylene, etc. As an aromatic vinyl compound, in terms of the high effect of improving the strength of the polymer (rubber), styrene and α-methylstyrene are preferred. The aromatic vinyl compound constituting the repeating unit (b) may be one or more.

[0031] The content of repeating units (b) in polymer (P) is 0% to 40% by mass relative to all repeating units of polymer (P). If the content of repeating units (b) exceeds 40% by mass, there is a tendency that the low hysteresis loss characteristics are insufficient when a cross-linked product (specifically, a cross-linked rubber) is prepared. Therefore, the content of repeating units (b) is preferably 37% by mass or less, more preferably 35% by mass or less, and further preferably 30% by mass or less relative to all repeating units of polymer (P). Polymer (P) may also be a polymer that does not have repeating units (b) (that is, the content of repeating units (b) is 0% by mass). On the other hand, by making polymer (P) into a copolymer containing conjugated diene compound units and aromatic vinyl compound units, the strength of the polymer can be further improved, which is preferred in this regard. The content of repeating units (b) is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more relative to all repeating units of polymer (P). In addition, the content of repeating units (b) in the polymer is determined by using 1 H-NMR ( 1 H-nuclear magnetic resonance, 1 H-NMR) device.

[0032] Repeating unit (c)

[0033] The repeating unit (c) is a repeating unit having a partial structure represented by the following formula (1).

[0034] [Chemistry 2]

[0035]

[0036] (In formula (1), n ​​is 0 or 1, R 1 represents a single bond or an alkylene group having 1 to 20 carbon atoms, R 2 ~R 4 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and "*" represents a bond to the polymer main chain)

[0037] In the formula (1), R 1 Examples of the hydrocarbylene group having 1 to 20 carbon atoms include a linear or branched alkanediyl group having 1 to 20 carbon atoms, a cycloalkylene group having 5 to 20 carbon atoms, an arylene group having 6 to 20 carbon atoms, and an aralkylene group having 7 to 20 carbon atoms.

[0038] In terms of suppressing the restriction of the movement of the partial structure (i.e., the side chain) represented by the formula (1) and further improving the strength of the cross-linked product obtained using the polymer (P), R 1 It is preferably a single bond or a linear or branched alkanediyl group having 1 to 20 carbon atoms, and more preferably a linear or branched alkanediyl group having 1 to 20 carbon atoms.

[0039] As R 2 ~R 4 Examples of the hydrocarbon group having 1 to 20 carbon atoms include a linear or branched alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms.

[0040] In terms of further improving the strength of the cross-linked product, R 2 It is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms, and more preferably a hydrogen atom or a linear or branched alkyl group having 1 to 3 carbon atoms.

[0041] R 3 and R 4 It is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms, and more preferably a hydrogen atom or a linear or branched alkyl group having 1 to 12 carbon atoms.

[0042] Here, in the repeating unit (c), two hydroxyl groups are respectively bonded to two adjacent carbons and carbons forming an aliphatic hydrocarbon structure. In the case where the carbon to which the hydroxyl group is bonded forms an aromatic ring, the distance between the hydroxyl groups is constant. In contrast, in the case where the carbon to which the hydroxyl group is bonded is a carbon forming an aliphatic hydrocarbon structure, the distance between the hydroxyl groups can be flexibly changed due to the rotation of the bond. Accordingly, the two hydroxyl groups in the repeating unit (c) are respectively easily able to obtain a distance suitable for interaction with other hydroxyl groups or reinforcing fillers. As a result, it can be considered that a higher elongation or breaking strength is shown compared to the case where the carbon to which the hydroxyl group is bonded forms an aromatic ring.

[0043] In terms of being able to more easily introduce the partial structure represented by the formula (1) into the side chain of the polymer and easily adjusting the content of the repeating unit (c) in the polymer (P), the repeating unit (c) is preferably a structural unit derived from a monomer having the partial structure represented by the formula (1) (hereinafter also referred to as "monomer (mc)").

[0044] Specific examples of the monomer (mc) include: 1,2-dihydroxyethyl (meth)acrylate, 1,2-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 1,2-dihydroxybutyl (meth)acrylate, 2,3-dihydroxybutyl (meth)acrylate, 3,4-dihydroxybutyl (meth)acrylate, 2,3-dihydroxy-1-methylpropyl (meth)acrylate, 1,2-dihydroxy 5-ethylhexyl ester, (meth)acrylate-9,10-dihydroxydecyl ester, 4,5-dihydroxy-2-pentenoic acid, 4,5-dihydroxy-2-hexenoic acid-tert-butyl ester, 5,6-dihydroxy-7-octenoic acid ethyl ester, 5,6-dihydroxy-8-nonenoic acid methyl ester, N-methyl-4,5-dihydroxy-2-octenyl isohydroxamic acid methyl ester, 2,3-dihydroxy-1-butene, 24,25-dihydroxy dammar-20-ene-3-one, etc.

[0045] In terms of the degree of reactivity, n in the formula (1) is preferably 1. In addition, as the monomer (mc), dihydroxyalkyl (meth)acrylate can be preferably used. The monomer (mc) constituting the repeating unit (c) may be one or more. In addition, in this specification, "(meth)acrylate" means including acrylate and methacrylate. "(Meth)acrylic group" means including acrylic group and methacrylic group.

[0046] The content of repeating units (c) in polymer (P) is 1% to 30% by mass relative to all repeating units of polymer (P). If the content of repeating units (c) is less than 1% by mass, it is difficult to show the effect of repeating units (c) and the strength improvement of the polymer cannot be fully achieved. If the content of repeating units (c) exceeds 30% by mass, rubber elasticity tends to no longer be shown. Therefore, the content of repeating units (c) is preferably 1.5% by mass or more, more preferably 2% by mass or more, relative to all repeating units of polymer (P). In addition, the content of repeating units (c) is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less, relative to all repeating units of polymer (P). In addition, the content of structural unit (c) in the polymer is determined by using 1 The value measured by H-NMR apparatus.

[0047] The polymer (P) may also have repeating units derived from compounds other than conjugated diene compounds, aromatic vinyl compounds and monomers (mc) (hereinafter also referred to as "other monomers") as monomer units constituting the polymer (P). As other monomers, for example, α,β-unsaturated nitrile compounds such as acrylonitrile, methacrylonitrile, and α-ethylacrylonitrile; unsaturated carboxylic acids such as (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid; unsaturated carboxylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate, etc. In the polymer (P), in terms of making low hysteresis loss characteristics, strength and processability good, the content of repeating units derived from other monomers relative to all repeating units of the polymer (P) is preferably 15% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, and further preferably 1% by mass or less.

[0048] <Method for producing polymer (P)>

[0049] The polymerization method for producing the polymer (P) is not particularly limited, and for example, block polymerization, suspension polymerization, emulsion polymerization, solution polymerization, etc. can be cited. The polymerization method is preferably an emulsion polymerization using an aqueous medium as a polymerization medium among these. As emulsion polymerization, known methods can be applied. Specifically, for example, the following method can be cited: utilizing an emulsifier to disperse the monomer in an aqueous medium (preferably in water), polymerizing in the presence of a polymerization initiator, and after reaching a desired polymerization conversion, adding a polymerization terminator to stop the polymerization.

[0050] When producing the polymer (P), it is preferable to use a monomer mixture containing a conjugated diene compound and the monomer (mc) as monomers and containing an aromatic vinyl compound as an optional component.

[0051] As emulsifiers, anionic surfactants, nonionic surfactants and amphoteric surfactants can be listed. In order to obtain a stable emulsified dispersion, anionic surfactants can usually be used. As anionic surfactants, for example, long-chain fatty acid salts, rosin acid salts, benzene sulfonates containing linear alkyl groups, etc. can be used. Specifically, potassium salts and sodium salts of capric acid, lauric acid, myristic acid, palmitic acid, oleic acid, stearic acid, octylbenzenesulfonic acid, dodecylbenzenesulfonic acid, dodecyldiphenyl oxide sulfonic acid and dodecyldiphenyl ether disulfonic acid can be listed. In addition, fluorine-based surfactants can also be used. As an emulsifier, one can be used alone or two or more can be used in combination.

[0052] As a polymerization initiator, a free radical polymerization initiator generally used in emulsion polymerization can be used. As a polymerization initiator, for example, organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, pinane hydroperoxide, paramenthane hydroperoxide, trimethyl bicycloheptyl hydroperoxide, di-tert-butyl hydroperoxide, and dicumyl peroxide can be used. In addition, diazo compounds represented by azobisisobutyronitrile, inorganic peroxides represented by potassium persulfate, and redox catalysts represented by a combination of these peroxides and ferrous sulfate can also be used. As a polymerization initiator, one or more types can be used alone or in combination. Relative to the total amount of 100 parts by mass of the monomers used in the polymerization, the amount of the polymerization initiator used is usually more than 0.01 parts by mass, preferably 0.05 parts by mass to 1.0 parts by mass.

[0053] During polymerization, a chain transfer agent may also be used to adjust the molecular weight of the polymer (P). Examples of chain transfer agents include alkyl mercaptans such as tert-dodecyl mercaptan and n-dodecyl mercaptan, carbon tetrachloride, thioglycols, diterpenes, terpinolene, γ-terpinenes, and α-methylstyrene dimers. As chain transfer agents, one may be used alone or two or more may be used in combination. The amount of chain transfer agent used is generally 0.05 parts by mass or more, preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the total amount of monomers used in the polymerization.

[0054] In addition, during emulsion polymerization, chelating agents such as sodium ethylenediaminetetraacetate, glycine, and alanine; electrolytes such as potassium chloride, sodium phosphate, potassium phosphate, and potassium sulfate; activators such as sodium formaldehydesulfoxylate and ferrous sulfate; pH adjusters such as ammonia, sodium hydroxide, and potassium hydroxide; and oxygen scavengers such as styrenated phenol, hindered phenol, imidazoles, p-phenylenediamine, and sodium bisulfite may be appropriately added.

[0055] In the production of the polymer (P) by emulsion polymerization, the polymerization method may be continuous or intermittent. A reactor after deoxygenation may be used, and the polymerization is usually carried out at a temperature of 0°C to 100°C, preferably at 0°C to 80°C. The polymerization time is preferably 1 hour to 24 hours, more preferably 2 hours to 12 hours. In addition, in the middle of the reaction, the operating conditions such as temperature or stirring may be appropriately changed, and a part of the monomer may be added to the reaction vessel in the middle of the polymerization.

[0056] In a polymerization reaction, gelation may sometimes occur if the polymerization conversion rate increases. Therefore, the polymerization conversion rate is preferably suppressed to below 85%, more preferably below 80%. It is particularly preferred to stop the polymerization within the range of 30% to 70% of the polymerization conversion rate. The polymerization can be stopped by adding a polymerization terminator at the time point when the desired polymerization conversion rate is reached. Examples of the polymerization terminator include hydroxylamine compounds such as hydroxylamine and N,N-diethylhydroxylamine; quinone compounds such as hydroquinone, etc. After the polymerization is stopped, unreacted monomers are removed from the reaction system by methods such as steam distillation as needed, thereby obtaining a latex in which the polymer (P) is dispersed in a dispersion medium.

[0057] The weight average molecular weight (Mw) of the polymer (P) obtained by the polymerization is preferably 1.0×10 5 If Mw is 1.0×10 5 The above values ​​tend to sufficiently improve the shape stability, tensile strength and wear resistance when a cross-linked product (specifically, a cross-linked rubber) is prepared, and thus the Mw of the polymer (P) is more preferably 1.2×10 5 More preferably, 1.5×10 5 In addition, the Mw of the polymer (P) is preferably 1.0×10 8 If Mw is 1.0×10 8 The Mw of the polymer (P) is more preferably 2.5×10 7 Below, more preferably 1.0×10 7 Below, more preferably 2.0×10 6 the following.

[0058] The preferred range of Mw of the polymer (P) can be determined by appropriately selecting the above-mentioned preferred upper limit and lower limit. The preferred range of Mw of the polymer (P) is 1.0×10 5 ~1.0×10 8 , the more preferred range is 1.0×10 5 ~2.5×10 7 , and the preferred range is 1.0×10 5 ~1.0×10 7 , and the more preferred range is 1.0×10 5 ~2.0×10 6 .

[0059] From the viewpoint of ease of manufacture, the molecular weight distribution (Mw / Mn) represented by the ratio of Mw to the number average molecular weight (Mn) of the polymer (P) is preferably 3.0 or more, more preferably 3.2 or more. In addition, from the viewpoint of making various properties of the cross-linked product good, the molecular weight distribution (Mw / Mn) is preferably 8.0 or less. In addition, in this specification, Mw and Mn of the polymer (P) are polystyrene conversion values ​​measured by gel permeation chromatograph (GPC).

[0060] The vinyl bond content of the polymer (P) is preferably 10% by mass to 25% by mass. If the vinyl bond content is 10% by mass or more, it is preferred in terms of sufficiently improving the wet grip characteristics when making a cross-linked rubber. In addition, if the vinyl bond content is 25% by mass or less, it is preferred in terms of obtaining a cross-linked rubber showing good low fuel consumption performance. The vinyl bond content of the polymer (P) is more preferably 11% by mass or more, further preferably 12% by mass or more, and further preferably 13% by mass or more. In addition, the vinyl bond content of the polymer (P) is more preferably 22% by mass or less, further preferably 20% by mass or less, and further preferably 18% by mass or less. In addition, in the present specification, the "vinyl bond content" is a value indicating the content ratio of repeating units having 1,2-bonds in the polymer (P) relative to the total amount of repeating units derived from butadiene, and is calculated using 1 The value measured by H-NMR apparatus.

[0061] As a method for producing the polymer (P), in addition to the above, it can also be obtained by the following method: a conjugated diene compound and, if necessary, an aromatic vinyl compound are copolymerized with a monomer having a reactive functional group (such as (meth)acrylic acid) to obtain a copolymer, and then a compound having a group reactive with the reactive functional group and having a hydroxyl group on an adjacent carbon is reacted with the copolymer.

[0062] 《Polymer composition》

[0063] By blending a crosslinking agent or the like into the polymer (P), a polymer composition for producing a crosslinked product (crosslinked rubber) used in the production of tires, etc. can be obtained. The polymer composition may also contain a filler (reinforcing filler) or other rubber components.

[0064] (Crosslinking agent)

[0065] As the crosslinking agent contained in the polymer composition of the present disclosure, sulfur, sulfur halide, organic peroxide, quinone dioxime, organic polyamine compound, alkylphenol resin having methylol group, etc. can be mentioned, and sulfur is usually used. The amount of sulfur blended is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the total amount of the rubber component contained in the polymer composition.

[0066] (Filler (reinforcing filler))

[0067] The reinforcing filler is used to increase the strength of the crosslinked product obtained by crosslinking the polymer (P). Examples of reinforcing fillers include silica, carbon black, an inorganic compound represented by the following formula (2) (hereinafter also referred to as "inorganic compound (M)"), reinforcing fibers (for example, inorganic fibers such as glass fibers or carbon fibers; organic fibers such as nylon or polyester), etc. Among these, the reinforcing filler is preferably at least one selected from the group consisting of silica, carbon black, and the inorganic compound (M).

[0068] nM 1 ·mSiO k ·iH2O…(2)

[0069] (In formula (2), M 1 is at least one selected from the group consisting of a specific metal, an oxide of a specific metal, and a hydroxide of a specific metal selected from any one of aluminum, magnesium, titanium, and calcium; n is an integer of 1 to 5, m is an integer of 0 to 10, k is an integer of 2 to 10, and i is an integer of 0 to 10)

[0070] As silica, for example, wet silica (hydrous silicic acid), dry silica (silicic anhydride), colloidal silica, precipitated silica, calcium silicate, aluminum silicate, etc. Among these, wet silica is particularly preferred from the perspective of improving the destructive properties of cross-linked rubber or the coexistence of wet grip and low hysteresis loss properties (low rolling resistance). In addition, from the perspective of making the dispersibility in the polymer composition good and improving the physical properties and processability, it is also preferred to use high-dispersible type silica. In addition, silica can be used alone or in combination of two or more. As carbon black, general purpose furnace black (GPF), fast extruding furnace black (FEF), high abrasion furnace black (HAF), intermediate super abrasion furnace black (ISAF), super abrasion furnace black (SAF), etc. can be listed, but there is no particular limitation. In addition, various reinforcing fillers such as clay and calcium carbonate may be further formulated in the polymer composition as inorganic fillers in addition to silica and carbon black.

[0071] Specific examples of inorganic compounds (M) include compounds in which the specific metal is aluminum, such as aluminum oxide, aluminum oxide monohydrate, aluminum hydroxide, aluminum carbonate, aluminum silicate, calcium aluminum oxide (Al2O3·CaO·2SiO4, etc.); compounds in which the specific metal is magnesium, such as magnesium oxide, magnesium hydroxide, magnesium carbonate, magnesium silicate, calcium magnesium silicate (CaMgSiO4), talc, etc.; compounds in which the specific metal is titanium, such as titanium oxide; compounds in which the specific metal is calcium, such as calcium oxide, calcium hydroxide, calcium carbonate, calcium silicate, etc.

[0072] As a reinforcing filler, one of silica, carbon black and inorganic compound (M) can be used alone, or two or more of these can be used in combination. In terms of the high effect of improving tire properties in combination with conjugated diene polymers, the polymer composition of the present disclosure preferably contains silica as a reinforcing filler, wherein wet silica, dry silica, and colloidal silica are preferably used. In the case of using a reinforcing filler, the amount of the reinforcing filler in the polymer composition (the total amount when containing two or more) is preferably 25 to 130 parts by mass, and more preferably 30 to 110 parts by mass, relative to the total amount of 100 parts by mass of the rubber component contained in the polymer composition.

[0073] (Other rubber components)

[0074] The polymer composition may further contain a rubber component different from the polymer (P) (hereinafter also referred to as "other rubber component"). In addition, in this specification, the so-called "rubber component" refers to a polymer that can obtain a hardened product showing rubber elasticity by hardening. The hardened product exhibits the following properties: a small force causes a large deformation at room temperature (for example, a deformation of more than 2 times when stretched at room temperature), and when the force is removed, it quickly returns to the original shape.

[0075] The other rubber components are polymers that do not contain at least one of the repeating units (a) and (c), and their types are not particularly limited. As other rubber components, for example, butadiene rubber (ButadieneRubber) (BR, such as high cis BR with cis-1,4-bonds of 90% or more), styrene butadiene rubber (SBR), natural rubber (Natural Rubber, NR), isoprene rubber (Isoprene Rubber, IR), styrene isoprene copolymer rubber, butadiene isoprene copolymer rubber, modified SBR (such as nitrogen-containing SBR, terminal modified SBR, etc.). The amount of other rubber components is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 50 parts by mass or less relative to the total amount of 100 parts by mass of the rubber components (polymer (P) and other rubber components) contained in the polymer composition.

[0076] In addition to the above components, various additives commonly used in polymer compositions for crosslinked products (crosslinked rubbers) such as anti-aging agents, zinc flower, stearic acid, softeners, vulcanization accelerators, silane coupling agents, compatibilizers, vulcanization aids, process oils, processing aids, and scorch retardants may be formulated in the polymer composition in addition to the above components. The formulation amounts of these may be appropriately selected according to the various components within the range that does not impair the effects of the present disclosure.

[0077] 《Manufacture of polymer compositions and cross-linked rubber》

[0078] The polymer composition of the present disclosure can be produced by mixing (specifically, kneading) components such as a reinforcing filler and the like, which are formulated as needed, in addition to the rubber component, using a kneading machine such as an open kneading machine (e.g., a roll) or a closed kneading machine (e.g., a banbury mixer).

[0079] In the kneading process, first, a rubber component containing a polymer (P) and an additive other than a vulcanization compounding agent (crosslinking agent, vulcanization accelerator, vulcanization aid) (hereinafter also referred to as "the first additive") are melt-kneaded using a kneading machine (the first process). The first additive preferably contains at least a reinforcing filler. The kneading temperature in the first process is appropriately set according to the melting point or glass transition point of the rubber component. By the melt kneading, the first additive is mixed with the rubber component, and the effects of improving the strength of the rubber product after vulcanization, making the kneading processability of the polymer composition good, or preventing the degradation of the rubber component caused by free radicals generated during kneading can be fully obtained.

[0080] Then, the kneaded product obtained by the first step is returned to room temperature as needed, a vulcanization agent is added to the kneaded product, and melt kneading is performed using a kneading machine (second step). The polymer composition obtained by the second step is molded and then crosslinked (vulcanized), thereby obtaining a crosslinked rubber as a crosslinked product.

[0081] 《Cross-linked materials and tires》

[0082] The crosslinked product (specifically, crosslinked rubber) obtained by using the polymer composition of the present disclosure can be applied to various rubber products. Specific examples of various rubber products include: tire applications such as tire tread, under tread, carcass, sidewall, bead part, etc.; sealing materials such as gaskets, gaskets, weather strips, O-rings, etc.; inner and outer packaging surface materials for various vehicles such as automobiles, ships, airplanes, and railways; building materials; vibration-proof rubbers for industrial machinery or equipment; various hoses and hose covers such as diaphragms, rollers, radiator hoses, and air hoses; belts such as power transmission belts; linings; dust boots; medical equipment materials; fenders; insulating materials for wires; other industrial products, etc.

[0083] The crosslinked product formed by crosslinking the polymer (P) is high-strength and is not prone to heat-induced strength reduction. Therefore, the polymer (P) is particularly suitable as a material for one or both of the tread and sidewall of the tire. According to the polymer (P), the components of the tire can be made thinner and resource saving can be achieved by increasing the strength of the rubber material, which is preferred in terms of the above aspect.

[0084] The tire can be manufactured by conventional methods. For example, the polymer (P) and the components formulated as needed are mixed using a mixer, and the polymer composition formed into a sheet is arranged at a predetermined position and vulcanized and formed according to conventional methods to form at least one of the tread or the sidewall, thereby obtaining a pneumatic tire.

[0085] According to the present embodiment described in detail above, the following aspects can be provided.

[0086] [1] A conjugated diene polymer comprising, relative to all repeating units, 45% to 99% by mass of repeating units (a) derived from a conjugated diene compound, 0% to 40% by mass of repeating units (b) derived from an aromatic vinyl compound, and 1% to 30% by mass of repeating units (c) derived from a monomer having a structure represented by the formula (1).

[0087] [2] The conjugated diene polymer according to [1], wherein R in the formula (1) 1 It is a single bond or a linear or branched alkanediyl group having 1 to 20 carbon atoms.

[0088] [3] The conjugated diene polymer according to [1] or [2], wherein the weight average molecular weight (Mw) in terms of polystyrene measured by gel permeation chromatography is 100,000 to 2,000,000.

[0089] [4] A polymer composition comprising the conjugated diene polymer according to any one of [1] to [3] and a cross-linking agent.

[0090] [5] The polymer composition according to [4], further comprising a filler.

[0091] [6] A cross-linked product obtained from the polymer composition according to [4] or [5].

[0092] [7] A tire at least partially using the cross-linked product according to [6].

[0093] Example

[0094] The following is a specific description based on examples, but the present disclosure is not limited to these examples. In addition, "parts" and "%" in the examples and comparative examples are based on mass unless otherwise specified. The following shows the measurement methods of various physical property values ​​of polymers.

[0095] [Repeating unit (c) content (%)], [bonded styrene content (%)], [vinyl bond content (%)]: measured using a 400 MHz 1The molecular weight of the monomer (mc) constituting the repeating unit (c) was calculated using the following formulas: A is the integral value of 6.0ppm to 7.5ppm, B is the integral ratio of 5.1ppm to 6.0ppm, C is the integral value of 4.5ppm to 5.1ppm, D is the integral value of 3.4ppm to 4.3ppm, m is the number of hydrogen atoms bonded to the carbon atom adjacent to the oxygen atom, and M is the molecular weight of the monomer (mc) constituting the repeating unit (c).

[0096] [Content of repeating unit (c) (%)] = (20D / m×M) / (4A×104)+5(2B+C)×54+(20D / m)×M}×100

[0097] [Bound styrene content (%)] = (4A × 104) / {(4A × 104) + 5 (2B + C) × 54 + (20D / n) × M} × 100

[0098] [Vinyl bond content (%)] = 2C / (2C+B) × 100

[0099] [Weight average molecular weight]: Calculated in terms of polystyrene from the retention time of a GPC curve obtained using a gel permeation chromatograph (HLC-8320GPC (trade name), manufactured by Tosoh Corporation).

[0100] (Measurement conditions)

[0101] Column: Two tubes of "GMHXL" (manufactured by Tosoh Corporation)

[0102] Column temperature: 40℃

[0103] Mobile phase: tetrahydrofuran

[0104] Flow rate: 0.4mL / min

[0105] Sample concentration: 10mg / 20mL

[0106] 1. Synthesis of conjugated diene polymers

[0107] [Example 1: Synthesis of vicinal diol-containing conjugated diene polymer A]

[0108] In a reactor (reactor) with an internal volume of 5L replaced with nitrogen, 1.5L of water, 49g of sodium dodecyl diphenyl oxide disulfonate, 1.24g of potassium chloride, 0.35g of sodium ethylenediaminetetraacetic acid salt (chelating agent), and 0.35g of sodium bisulfite were added. Next, 25mL of water containing 0.44g of sodium ethylenediamineacetic acid salt, 0.18g of ferrous sulfate, and 0.70g of sodium formaldehyde sulfoxylate, 2.45g of tert-dodecyl mercaptan, 512g of 1,3-butadiene, 181g of styrene, and 7g of 2,3-dihydroxypropyl methacrylate were added. After stirring at 330rpm and adjusting the temperature of the reactor contents to 10°C, 1.33g of pinane hydroperoxide was added to initiate polymerization. Polymerization was carried out under temperature control conditions (10°C). At the time point when the polymerization conversion rate reached 70%, 4.94mL of 6.2% N,N-diethylhydroxylamine aqueous solution was added to stop the polymerization reaction. In a stripping tank, the pressure was reduced to -0.1 MPa, and then the temperature was raised to 60°C and stripping was performed for 30 minutes to remove residual monomers, thereby obtaining a latex.

[0109] Next, 89 g of calcium chloride and 4.2 g of potassium hydroxide were added to 9.15 L of warm water at 50° C. and dissolved, and the latex obtained in the polymerization was added to the aqueous solution to coagulate the rubber component. Thereafter, the rubber was washed with water at 50° C., 50° C., and 20° C. in sequence, and dried with a roll at a temperature of 130° C. to obtain a vicinal diol-containing conjugated diene polymer A.

[0110] [Example 2: Synthesis of vicinal diol-containing conjugated diene polymer B]

[0111] A vicinal diol-containing conjugated diene polymer B was obtained in the same manner as in Example 1 except that the amount of 1,3-butadiene used was changed to 491 g and the amount of 2,3-dihydroxypropyl methacrylate used was changed to 28 g.

[0112] [Example 3: Synthesis of vicinal diol-containing conjugated diene polymer C]

[0113] A vicinal diol-containing conjugated diene polymer C was obtained in the same manner as in Example 1 except that the amount of 1,3-butadiene used was changed to 309 g and the amount of 2,3-dihydroxypropyl methacrylate used was changed to 210 g.

[0114] [Example 4: Synthesis of vicinal diol-containing conjugated diene polymer D]

[0115] A vicinal diol-containing conjugated diene polymer D was obtained in the same manner as in Example 1 except that the amount of 1,3-butadiene used was changed to 463 g and 56 g of 9,10-dihydroxydecyl methacrylate was used instead of 2,3-dihydroxypropyl methacrylate.

[0116] [Comparative Example 1: Synthesis of vicinal diol-containing conjugated diene polymer E]

[0117] A vicinal diol-containing conjugated diene polymer E was obtained by the same method as in Example 1 except that the amount of 1,3-butadiene used was changed to 518 g and the amount of 2,3-dihydroxypropyl methacrylate used was changed to 1 g.

[0118] [Comparative Example 2: Synthesis of vicinal diol-containing conjugated diene polymer F]

[0119] A vicinal diol-containing conjugated diene polymer F was obtained by the same method as in Example 1 except that the monomers and amounts used in the polymerization were changed to 239 g of 1,3-butadiene, 181 g of styrene, and 280 g of 2,3-dihydroxypropyl methacrylate.

[0120] [Comparative Example 3: Synthesis of Hydroxyl-Containing Conjugated Diene Polymer G]

[0121] A vicinal diol-containing conjugated diene polymer G was obtained by the same method as in Example 1 except that 28 g of 3-hydroxypropyl methacrylate was used instead of 2,3-dihydroxypropyl methacrylate in the polymerization recipe.

[0122] [Comparative Example 4: Synthesis of Unmodified Conjugated Diene Polymer H]

[0123] In a reactor (reactor) with an internal volume of 100 L replaced with nitrogen, 36.8 L of water, 1190 g of sodium dodecyl diphenyl oxide disulfonate, 6.7 g of potassium chloride, 8.5 g of sodium ethylenediaminetetraacetic acid salt (chelating agent), and 8.5 g of sodium bisulfite were added. Next, 638 mL of water containing 10.6 g of sodium ethylenediamineacetic acid salt, 4.3 g of ferrous sulfate, and 17.0 g of sodium formaldehyde sulfoxylate, 51 g of tert-dodecyl mercaptan, 11883 g of 1,3-butadiene, and 4403 g of styrene were added. After stirring at 330 rpm and adjusting the temperature of the reactor contents to 10°C, 17.0 g of pinane hydroperoxide was added to initiate polymerization. Polymerization was carried out under temperature control conditions (10°C). At the time point when the polymerization conversion rate reached 70%, 1.65 L of 6.2% N,N-diethylhydroxylamine aqueous solution was added to stop the polymerization reaction. In the stripping tank, the pressure was reduced to -0.1 MPa, and then the temperature was raised to 60°C, and stripping was performed for 30 minutes to remove the residual monomers, thereby obtaining a latex.

[0124] Next, 1.79 kg of calcium chloride was added to 183 L of warm water at 50° C. and dissolved, and the latex obtained in the polymerization was added to the aqueous solution to coagulate the rubber component. Thereafter, the rubber was washed with water at 50° C., 50° C., and 20° C. in sequence, and dried in a hot air dryer adjusted to 90° C., thereby obtaining an unmodified conjugated diene polymer H.

[0125] 2. Production and evaluation of polymer compositions and cross-linked products

[0126] [Examples 1 to 4 and Comparative Examples 1 to 4]

[0127] The conjugated diene polymers A to H manufactured in the above-mentioned method are respectively used to prepare each component according to the formulation formula shown in Table 1, and knead them to manufacture a polymer composition. The kneading is carried out in the following method. Using a Plasto mill (content: 250 mL) with a temperature control device, the conjugated diene polymers (A to H), a vulcanization accelerator and sulfur are mixed and kneaded under the conditions of a filling rate of 72% and a rotation speed of 60 rpm. The obtained polymer composition is molded and vulcanized for a specified time at 160°C using a vulcanization press to obtain a cross-linked product (vulcanized rubber).

[0128] The following tensile test was performed using the obtained cross-linked product (vulcanized rubber). Table 1 shows the evaluation results based on the tensile test.

[0129] (Tensile test)

[0130] According to Japanese Industrial Standards (JIS) K6251: 2017, using dumbbell-shaped No. 3 test pieces, the tensile stress at 100% elongation (M100), tensile strength (TB), elongation at break (EB), and half value (=TB×EB÷2) of the tensile product (=TB×EB) were determined.

[0131]

[0132] In Table 1, “vulcanization accelerator CZ” used was “Nocceler CZ” manufactured by Ouchi Shinko Chemical Co., Ltd. and “sulfur” used was “Kinhua Inspur Micro Powder Sulfur 200 Mesh” manufactured by Tsurumi Chemical Co., Ltd.

[0133] From the results shown in Table 1, it can be said that the crosslinked product using the conjugated diene polymer containing a structural unit having a partial structure in which two hydroxyl groups are bonded to adjacent carbon atoms in a certain ratio has higher strength than the crosslinked product of the comparative example.

[0134] When examined in more detail, Examples 1 to 4 have good balances in tensile stress (M100), tensile strength (TB), elongation at break (EB), and tensile product, and exhibit high-strength physical properties. In contrast, the crosslinked product of Comparative Example 1 using a conjugated diene polymer having a repeating unit (c) content as low as 0.2% and the crosslinked product of Comparative Example 4 using a conjugated diene polymer having no repeating unit (c) have good tensile stress (M100), but have low tensile strength (TB), elongation at break (EB), and tensile product compared to Examples 1 to 4. In addition, the crosslinked product of Comparative Example 2 using a conjugated diene polymer having a repeating unit (c) content as high as 40% has high tensile stress (M100) and low elongation at break (EB) and tensile product. The crosslinked product of Comparative Example 3 using a conjugated diene polymer introduced with a repeating unit having only one hydroxyl group instead of the repeating unit (c) had lower tensile strength (TB) and tensile product than those of Examples 1 to 4.

[0135] <Production and evaluation of filler-containing polymer compositions and cross-linked products>

[0136] [Examples 5 to 9 and Comparative Examples 5 to 7]

[0137] The respective components were blended according to the formulation shown in Table 2 and kneaded to produce a filler-containing polymer composition. The kneading was performed in the following manner.

[0138] A batch mixer equipped with a temperature control device (manufactured by Toyo Seiki Seisaku-sho Co., Ltd.; trade name: Labo Plasto Mill) was used. As the first stage of kneading, the set temperature was adjusted to 100° C., and the rubber component, filler, silane coupling agent, extender oil, stearic acid, antioxidant and zinc oxide were mixed and kneaded under the conditions of a filling rate of 70%, a rotation speed of 60 rpm and a kneading time of 4 minutes. In addition, in Examples 8 and 9 and Comparative Example 7, a resin was further mixed and kneaded.

[0139] Then, as the second stage of mixing, after the mixed material obtained by the mixing of the first stage is cooled to room temperature, the vulcanization accelerator and sulfur are deployed in the mixer, the set temperature is adjusted to 70°C, and the mixing is carried out under the conditions of a rotation speed of 60rpm and a mixing time of 1.5 minutes, thereby obtaining the formulations respectively. The temperature of the mixed material discharged from the mixer when discharged is all below 100°C. Then, each obtained formulation is vulcanized and formed for a predetermined time at 160°C using vulcanization pressing, thereby obtaining a vulcanized rubber as a cross-linked product. Using the obtained vulcanized rubber, the following physical property evaluations are performed. The results are shown in Table 2.

[0140] [Evaluation method of formulation properties]

[0141] Strength (TB×EB÷2)

[0142] The vulcanized rubber was used as a test sample and a tensile test was performed in accordance with JIS K6251:2010. Here, a dumbbell No. 3 shape was used as a test sample, and the stress at break (TB, unit: MPa) and the elongation at break (EB, unit: %) were measured at room temperature. In addition, the half value of the tensile product (=TB×EB) was calculated using the measured values. The calculated results are shown in Table 2 for Examples 5 and 6, with Comparative Example 5 being 100, for Example 7, with Comparative Example 6 being 100, and for Examples 8 and 9, with Comparative Example 7 being 100. A larger value indicates a higher strength.

[0143]

[0144] In Table 2, the details of the reagents and the like used are as follows.

[0145] *1) BR01 manufactured by ENEOS Material, *2) ZEOSIL 1165MP manufactured by Solvay, *3) Diamond black N330 manufactured by Mitsubishi Chemical Corporation, *4) Hygilite H-43M manufactured by Showa Denko Co., Ltd., *5) Si75 manufactured by Evonik, *6) T-REZ PR802 manufactured by ENEOS, *7) Processing oil T-DAE manufactured by ENEOS, *8) Ozonone 6C manufactured by Seiko Chemical, *9) Nocceler D manufactured by Ouchi Shinko Chemical, *10) Nocceler CZ-G manufactured by Ouchi Shinko Chemical

[0146] In Table 2, polymers A to D and polymer H represent conjugated diene polymers synthesized in Examples 1 to 4 and Comparative Example 4, respectively.

[0147] From the results shown in Table 2, it can be said that a cross-linked product obtained by cross-linking a polymer (P) having repeating units derived from a monomer in which two hydroxyl groups are bonded to adjacent carbon atoms at a predetermined ratio and a filler or the like is mixed and the resulting mixture is higher in strength than a cross-linked product of a comparative example using only a polymer different from the polymer (P) as a rubber component.

Claims

1. A conjugated diene polymer comprising, relative to all repeating units, 45% to 99% by mass of repeating units (a) derived from a conjugated diene compound, 0% to 40% by mass of repeating units (b) derived from an aromatic vinyl compound, and 1% to 30% by mass of repeating units (c) having a partial structure represented by the following formula (1). [Chemistry 1] (In formula (1), n ​​is 0 or 1, R 1 represents a single bond or an alkylene group having 1 to 20 carbon atoms, R 2 ~R 4 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and "*" represents a bond to the polymer main chain.

2. The conjugated diene polymer according to claim 1, wherein In the formula (1), R 1 It is a single bond or a linear or branched alkanediyl group having 1 to 20 carbon atoms.

3. The conjugated diene polymer according to claim 1 or 2, wherein The weight average molecular weight (Mw) in terms of polystyrene measured by gel permeation chromatography is 100,000 to 2,000,000.

4. A polymer composition comprising the conjugated diene polymer according to claim 1 and a crosslinking agent. The polymer composition according to claim 4 , further comprising a filler.

6. A cross-linked product obtained from the polymer composition according to claim 4 or 5.

7. A tire at least partially using the cross-linked product according to claim 6.

Citation Information

Patent Citations

  • Silica-filled rubber composition and molded article

    JP2004256801A

  • Bale of conjugated diene polymer composition, tire, and method for producing bale of conjugated diene polymer composition

    JP2019182996A

  • Inspection device

    JP2022147890A